Intervertebral disc herniation effects on multifidus muscle composition and resident stem cell populations. Issue 2 (6th May 2020) - Agha, Obiajulu; Mueller‐Immergluck, Andreas; Liu, Mengyao; Zhang, He; Theologis, Alekos A.; Clark, Aaron; Kim, Hubert T.; Liu, Xuhui; Feeley, Brian T.; Bailey, Jeannie F.
Absract: Background: Paraspinal muscles are crucial for vertebral stabilization and movement. These muscles are prone to develop fatty infiltration (FI), fibrosis, and atrophy in many spine conditions. Fibro‐adipogenic progenitors (FAPs), a resident muscle stem cell population, are the main contributors of muscle fibrosis and FI. FAPs are involved in a complex interplay with satellite cells (SCs), the primary myogenic progenitor cells within muscle. Little is known about the stem cell composition of the multifidus. The aim of this study is to examine FAPs and SCs in the multifidus in disc herniation patients. Multifidus muscle samples were collected from 10 patients undergoing decompressive spine surgery for lumbar disc herniation. Hamstring muscle was collected from four patients undergoing hamstring autograft ACL reconstruction as an appendicular control. Multifidus tissue was analyzed for FI and fibrosis using Oil‐Red‐O and Masson's trichrome staining. FAPs and SCs were visualized using immunostaining and quantified with fluorescence‐activated cell sorting (FACS) sorting. Gene expression of these cells from the multifidus were analyzed with reverse transcription‐polymerase chain reaction and compared to those from hamstring muscle. FI and fibrosis accounted for 14.2%± 7.4% and 14.8%±4.2% of multifidus muscle, respectively. The multifidus contained more FAPs (11.7%±1.9% vs 1.4%±0.2%; P <.001) and more SCs (3.4%±1.6% vs 0.08%±0.02%; P =.002) than the hamstring. FAPs had greater α Smooth Muscle Actin (αSMA) and adipogenic gene expression than FAPs from the hamstring. SCs from the multifidus displayed upregulated expression of stem, proliferation, and differentiation genes. Conclusion: The multifidus in patients with disc herniation contains large percentages of FAPs and SCs with different gene expression profiles compared to those in the hamstring. These results may help explain the tendency for the multifidus to atrophy and form FI and fibrosis as well as elucidate potential approaches for mitigating these degenerative changes by leveraging these muscle stem cell populations. Abstract : Paraspinal muscles are known to develop muscle fatty infiltration (FI), fibrosis, and atrophy in a number of spine conditions, including intervertebral disc herniation. In this study, we histologically examined multifidus muscle specimens harvested from patients undergoing spine surgery for the degree of degenerative muscle pathology and characterized fibro‐adipogenic progenitors (FAPs) and Satellite cells (SCs) within the muscle in terms of quantity and gene expression profiles. We discovered a high degree of FI and fibrosis in the multifidus as well as large quantities of FAPs and SCs that displayed different gene expression profiles than those taken from healthy hamstring muscle controls.